Applications of Computational Tools in Biosciences and Medical Engineering - Öchsner, Andreas; Altenbach, Holm (Advanced Structured Materials, 2015)
This book presents the latest developments and applications of computational tools related to the biosciences and medical engineering. It also reports the findings of different multi-disciplinary research projects, for example, from the areas of scaffolds and synthetic bones, implants and medical devices, and medical materials. It is also shown that the application of computational tools often requires mathematical and experimental methods. Computational tools such as the finite element methods, computer-aided design and optimization as well as visualization techniques such as computed axial tomography open up completely new research fields that combine the fields of engineering and bio/medical. Nevertheless, there are still hurdles since both directions are based on quite different ways of education. Often even the "language" can vary from discipline to discipline.